PENDEKATAN REGRESI NONPARAMETRIK SPLINE TRUNCATED PADA INDEKS PEMBANGUNAN MANUSIA DI SULAWESI SELATAN - Selvi Meilinda; Sudarmin Sudarmin; Muhammad Nusrang (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2021)
The human development index is an improvement in the quality of life for the society which is used as a benchmark for human development which consists of 3 basic aspects, namely health, education, and life worthiness. In South Sulawesi, the Human Development Index (HDI) has been categorized as high even though its growth tends to slow down. There are several factors that are thought to influence HDI in South Sulawesi, namely, Life Expectancy, Average Length of Schooling, Population Percentage, Morbidity Rate, and Gross Regional Domestic Product (GRDP). Modeling is done by using the spline truncated nonparametric regression analysis method with the Generalized Cross-Validation (GCV) approach to obtain the best optimal value that is the minimum optimal value. The results of this study indicate that based on the fishery significance test of the model parameters, it can be seen that there are variables that significantly influence the Human Development Index in South Sulawesi, namely Gross Regional Domestic Product (x5). Based on the research, the minimum GCV value was 0.08 which was obtained from 3 knots with a value of 90.94%.Keywords: GCV, Human Development Index, Spline Truncated Nonparametric Regression